From Victims to Survivors: Holocaust Survivor's Adaptation to Life in Wisconsin - Rolbiecki, Monica R. (My University, 2012)
This paper will explore the post World War II (WWII) adaptation experience of Holocaust survivors to life in Wisconsin. It will discuss how well they adapted as well as why; the focus will be on their work, the support they received and anti-Semitism they faced in Wisconsin. Another theme that will be expanded on is their unwillingness to discuss the experiences that had occurred during WWII, and whether this led to difficulties in adapting to life in Wisconsin or helped to make the process a positive one.
Keywords: Antisemitism--Wisconsin; Holocaust survivors--Social conditions--Wisconsin; Holocaust survivors--Psychology; Holocaust survivors--Wisconsin